Safety of Pegfilgrastim (Neulasta) in Patients with Sickle Cell Trait/Anemia - Pashtoon Murtaza Kasi; Mrinal M. Patnaik; Prema P. Peethambaram (Case Reports in Hematology)
Pegfilgrastim (Neulasta) is a recombinant filgrastim (human granulocyte colony-stimulating factor (G-CSF)) attached to a polyethylene glycol (PEG) molecule and is given as part of chemotherapy regimens that are associated with significant myelosuppression and risk for febrile neutropenia. Prescribing information available on manufacturer’s website for the drug warns us about possible severe sickle cell crises related to the medication but does not report the actual incidence or the use in patients with sickle cell trait. Caution is advised when using it in patients with sickle cell disease. Here we present a case of a Caucasian female with known sickle cell trait (SCT) with no prior complications who developed a presumed sickle cell crisis after getting Neulasta, as a part of the chemotherapy regimen used to treat her breast cancer. Based on our literature review, this appears to be the first case report of a patient with SCT developing a sickle cell crisis with the pegylated form of recombinant filgrastim. Given the dearth of literature regarding the use of G-CSF and its related pegylated forms in patients with sickle cell anemia and sickle cell trait, a discussion of potential mechanisms and review of current literature and guidelines is also presented.